Trend and need of Application Virtualization In Cloud Computing (Global Journal of Computer Science and Technology, 2013)
As the variety of applications increases so does the complexity of delivering and managing those applications also increases, many organizations tried to manage that complexity by standardizing on a fixed portfolio of applications in a locked-down configuration. This approach reduces the IT labour costs, but the restrictions involved lead to a frustrating user experience and constraints on flexibility and business agility. Thus This paper presents a better solution that would enable IT to deliver and manage applications at reduced cost while enabling flexibility and agility. Here the concept of application virtualization which is a part of virtualization and how application virtualization is used by cloud computing to deliver application with fast speed, reliability and flexibility shall be discussed.
Keywords: application virtualization; standalone; streaming; saas; agent based; agent less